Idiopathic Premature Ventricular Contractions From the Outflow Tract Display an Underlying Substrate That Can Be Unmasked by a Type 2 Brugada Electrocardiographic Pattern at High Right Precordial Leads - Parreira, Leonor; Marinheiro, Rita; Carmo, Pedro; Mesquita, Dinis; Farinha, José; Amador, Pedro; Ferreira, António; Fonseca, Marta; Costa, Francisco; Cavaco, Diogo; Caria, Rui; Adragão, Pedro (Frontiers in Physiology, 2020)
Background: Patients with premature ventricular contractions (PVCs) from the right ventricular outflow tract (RVOT) and apparently normal hearts, can have ST elevation similar to type 2 or type 3 Brugada pattern in the electrocardiographic (ECG) performed at a higher position. Cardiac magnetic resonance (CMR), has shown conflicting data regarding existence of structural abnormalities in patients with idiopathic PVCs from the RVOT. Objective: Our aim was to evaluate the prevalence of low voltage areas (LVAs) in the RVOT of patients with PVCS from the outflow tract, and in a control group. Secondly, assess for the presence of a non-invasive ECG marker. Methods: A 56 consecutive patients, 45 with frequent PVCs (>10000/24 h) LBBB, vertical axis, negative in aVL and 11 subjects without PVCs. Arrhythmogenic right ventricular cardiomyopathy was ruled out in all patients. An ECG was performed with V1–V2 at the level of the second intercostal space and the presence of ST-segment elevation with a Type 2 or 3 Brugada pattern (Type 2 BrP) was assessed. Bipolar voltage map of the RVOT was performed in sinus rhythm (0.5–1.5 mV color display). Areas with electrograms <1.5 mV represented the LVA. The area adjacent to the pulmonary valve usually displays voltage between 0.5 and 1.5 mV and is classified as transitional-voltage zone. Presence of LVAs outside this transitional-voltage zone were estimated. We compared two groups with and without ST-segment elevation and tested for the association between ECG pattern and LVAs. Results: None of the patients in the control group had ST-segment elevation or LVAs. In the PVC group, no patient had type 1 Brugada pattern, 29 patients (64%) had type 2 or 3 ST-segment elevation (Type 2 BrP), and 28 (62%) had LVAs outside the transitional-voltage zone. LVAs were more frequent in patients with Type 2 BrP; 93% versus 4%, p < 0.0001. The ECG pattern was associated with the presence of LVAs, OR (95% CI): 202.50 (16.92–2423), p < 0.0001. Conclusion: Low voltage areas were frequently present in the RVOT of patients with idiopathic PVCs. They were absent in controls and can be unmasked by the presence of Type 2 BrP in high right precordial leads.